Effectiveness of Using Online Single Submission Applications - Risti Sutar; Muh Nasrullah; Isgunandar (Journal of Social Science and Economics (JOSSE), 2024)
Effectiveness refers to how an organization successfully achieves its goals by measuring and assessing performance in carrying out tasks or activities. This study aims to evaluate how effective the use of the Online Single Submission Application is at the Office of the Investment and One-Stop Integrated Service of South Sulawesi Province. This study is important to identify factors that support or hinder the effectiveness of the use of the OSS application. The research method used is descriptive with a qualitative approach, which describes how the use of the OSS application takes place in the office. Data were collected through observation, interviews, and documentation. The study shows that the implementation of the Online Single Submission Application at the Office of the Investment and One-Stop Integrated Service of South Sulawesi Province was considered successful. Informants were satisfied with the clarity of the strategy for achieving goals, the quality of policy analysis, careful planning, the preparation of appropriate programs, and adequate work facilities. Good implementation, an effective monitoring system, and strict control also play a role in maintaining information security and preventing unauthorized access.